2021
DOI: 10.1109/access.2021.3069409
|View full text |Cite
|
Sign up to set email alerts
|

Silver Sandwiched ITO Based Transparent Antenna Array for RF Energy Harvesting in 5G Mid-Range of Frequencies

Abstract: A transparent antenna array based on silver sandwiched indium tin oxide (AgITO) heterostructure thin films is presented. The AgITO is sputtered on both sides of soda-lime glass (SLG) substrate, and the three thin films deposition parameters are optimized to obtain very low ohmic interfacial contact resistance of less than 1 Ω/Sq. AgITO promotes thin film-based transparent microstrip structure of the proposed antenna array as well as the transparent T-junction power divider. Furthermore, AgITO microstrip as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Many literature have demonstrated that TAs with TCFs can replace traditional antennas and take advantage of their transparency in a variety of environments. TAs using TCFs has been applied on the solar panel of CubeSat, the screen of mobile phone, automotive communications, smart glasses and so on [19][20][21][22][23][24][25]. The transparent characteristic of TAs allows them to be applied to any surface without limitation [26].…”
Section: Introductionmentioning
confidence: 99%
“…Many literature have demonstrated that TAs with TCFs can replace traditional antennas and take advantage of their transparency in a variety of environments. TAs using TCFs has been applied on the solar panel of CubeSat, the screen of mobile phone, automotive communications, smart glasses and so on [19][20][21][22][23][24][25]. The transparent characteristic of TAs allows them to be applied to any surface without limitation [26].…”
Section: Introductionmentioning
confidence: 99%
“…One of the emerging countermeasures is to harvest energy available in radio frequency (RF) signals surrounding communications devices. Presently, 5G/6G devices deploy successfully cheap energy harvesting (EH) integrated circuits [ 5 , 6 , 7 , 8 ]. Nonetheless, a plurality of performance analyses pertinent to RF EH has featured EH to be linear for simplicity [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The substrate material and the conductive material of the antenna are key factors for the light transmission, flexibility, and stretchability of the antenna. So far, a variety of transparent substrates have been used to manufacture transparent antennas, including glass [1,3,12,13,[17][18][19], polyimide (PI) [2], polydimethylsiloxane (PDMS) [5], plexiglass [6], polyethylene terephthalate (PET) [7,20,21], polyvinyl chloride (PVC), and Ecoflex™. These materials are different in various aspects, such as dielectric properties, hardness, brittleness, and light transmission.…”
Section: Introductionmentioning
confidence: 99%